Hubungan Antara Kesetaraan Gender Terhadap Sikap Memilih Jurusan pada Siswa SMA X di Kabupaten Klaten - Tri Welas Asih; Muslimah Zahro Romas; Eni Rohyati (Jurnal Psikologi, 2019)
This research is aimed to knowing the relations between gender equality toward the actions in choosing major of the students of SMA X in Klaten Regency. The more of major which perceived as masculine major, they were interested by female students. Also on the other hand, a lot of male students who are interested to take major that identic to the nature of feminine.The kind of this research is quantitative research using collecting data by scale. The subject of this research are students of grade XII of SMA X in Klaten Regency. Data analysis technique used a correlation of Product Moment of Pearson.The research result shows that a correlation coefficient rxy=0,376 and p=0,001 (p<0,01). It means that there is a positive relationship between gender equality toward the action in choosing major of the students of SMA X in Klaten Regency. Effective contributions the gender equality toward the actions in choosing major totaling 14,13 % than other factors. The conclusion of this research is the higher the understanding of gender equality, therefore the higher of actions in choosing major of students of SMA X in Klaten Regency. Keyword: Gender Equality, Actions, Choosing Major